The role of centralized knowledge development centre for success of SME sector - Narayanasamy, Kogilah; Shetty, M. V. (IBIMA Publishing, 2008)
The aim of the current study was to asses the importance of a Centralized Knowledge Development Centre for the progress of the SMEs' in Malaysia and factors that influence SMEs' favorable attitude and barriers that hinder them from adopting this usage in their business. SME is the heart of any national development both from an economy point of view as well as employment. Further SME has to handle a diverse portfolio of things in as short a time as possible and with the minimum manpower they can garner from within their small outfits. Knowledge Management would make it possible, but creating a Knowledge Management system is costly and beyond the professional levels or cost considerations of the SME sector, however it is an important initiative so as to have a competitive edge in this dynamic environment, where the latest information is the key to success. Enterprises needs solution based on customized information at a rapid pace, which is possible for the small sector, due to the nimble nature of this sector, if they had the basic information and knowledge of the requirements. Knowledge Management also enables one to become a global player even in their greenfield project if the right information of global needs and consumer preferences, prices etc are available. The questions that arise are: Given this situation, the major questions that arise are: "How can SMEs be encouraged to participate collectively in this KDC?" "Why is the encouragement mediocre with no special focus into training and development and incentives created for them?" "Why have there not been any in-depth studies of this emerging area till date so that there would have been major technological breakthroughs?" It is opined that if there is a Centralized Knowledge Development Centre created professionally, the SME sector would benefit immensely. Though many issues would remain unaddressed even after our study, a fairly good glimpse is expected to be available to the researchers in this regard. Nevertheless a study of the likely benefits as perceived by the SME sector is felt interesting and useful for academicians, policy makers and the industries attempting this development.